A predictive factor for axillary lymph node metastasis in invasive ductal breast cancer: the value of tumor and breast volume ratio - Kubat, Mehmet; Dinç, Soykan (International Surgery Journal, 2018)
Background: The objective of this study was to witness the effect of tumor volume/breast volume ratio on the presence of axillary lymph node metastasis and to examine the strategy in surgical treatment approach for patients. Methods: This study was carried out prospectively by examining the patients undergoing modified radical mastectomy surgery due to breast cancer (n=99). Breast volumes were measured through liquid overflow method in graduated bowl tumor volume was measured according to ellipsoid volume formula with diameters determined by pathological specimen, ultrasonography or MRI. Results: Axillary lymph node metastasis (ALNM) was positive in 64.6% of them (n=64). Average breast volume was found to be 693.89cm³ in the measurement of mastectomy materials. Average tumor volume was found to be 9.58cm³. In line with these results, average tumor volume/breast volume (vTm/vMm) ratio was: 0.0176. Author found axillary lymph node metastasis possibility significantly higher in patients with vTm/vMm ratio>0.016 (Odds ratio 9.437, p-value 0.007). Conclusions: The presence of ALNM is the most important factor in indicating the prognosis of patients with invasive breast cancer and planning the treatment. Thus, knowing whether there exists an ALNM or not during preoperative period draws the attention of both the doctors performing treatment and patients. In this study efficiencies of largest tumor diameter, tumor volume and tumor volume (vTm)/Breast volume (vMm) ratio in indicating ALNM presence in cases with T2 invasive ductal breast cancer were evaluated. It was found that vTm/vMm ratio was a recent and effective prognostic criterion in determining ALNM.